SOCIETY FOR ENDOCRINOLOGY ENDOCRINE EMERGENCY GUIDANCE: Acute management of the endocrine complications of checkpoint inhibitor therapy. Issue 7 (July 2018) - Higham, C E; Olsson-Brown, A; Carroll, P; Cooksley, T; Larkin, J; Lorigan, P; Morganstein, D; Trainer, P J; ,
Abstract : Immunotherapy treatment with checkpoint inhibitors (CPI) (CTLA-4 and PD-1 inhibitors) significantly improves survival in a number of cancers. Treatment can be limited by immune-mediated adverse effects including endocrinopathies such as hypophysitis, adrenalitis, thyroiditis and diabetes mellitus. If endocrinopathies (particularly hypocortisolemia) are not recognized early, they can be fatal. The diagnosis and management of endocrinopathies can be complicated by simultaneous multi-organ immune adverse effects. Here, we present Endocrine Emergency Guidance for the acute management of the endocrine complications of checkpoint inhibitor therapy, the first specialty-specific guidance with Endocrinology, Oncology and Acute Medicine input and endorsed by the Society for Endocrinology Clinical Committee. We present algorithms for management: endocrine assessment and management of patients in the first 24 hours who present life-threateningly unwell (CTCAE grade 3–4) and the appropriate management of mild-moderately unwell patients (CTCAE grade 1–2) presenting with features compatible with an endocrinopathy. Other important considerations in relation to hypohysitis and the maintenance of glucocorticoid therapy are discussed.